LAUTAN DALAM PENYELENGGARAAN DESENTRALISASI : PERGESERAN PARADIGMA MENUJU KESEJAHTERAAN MASYARAKAT LOKAL BERBASIS KELAUTAN - Kartikaningsih, Meita Ahadiyati (Jurnal Desentralisasi, 2012)
Local government has an important role to optimize the potential of marine regions, as this has been among decentralized affairs. However, with the drawback in the decentralization policies and capacity issues of local goverments in carrying out business in the maritime field, the vast potential of the oceans have not become a basis for increasing social welfare. Moreover, local government policies tend to be oriented to promote local own revenue and the scope of activities need to be diversified beyond fishery economy. With the dimishing resources in the mainland, sea potential can be a beacon of hope for development, especially in the regions. However, to ?shift? the development paradigm towards the development of marine, strong commitment of the government is required. This paper attempts to offer a variety of ideas that can be taken from perspective of local government to optimize the utilization of potential of marine for the welfare of society within the principles of blue economy.